Linguistic Threads in ‘Cardigan’ Song Lyrics: A Study of Bound and Free Morphemes - Erniyanti Nur Fatahhela Dewi; Mentari Pratami (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study examines the use of bound and free morphemes in Taylor Swift’s Cardigan to explore how morphological structure contributes to meaning in contemporary song lyrics. The purpose of this research is to investigate how morphological elements contribute to linguistic artistry, thematic cohesion, and emotional intensity in popular music. Employing a qualitative descriptive research design, the study analyzes words and phrases containing free and bound morphemes drawn from the officially published lyrics of Cardigan. Data were collected through documentation techniques and analyzed using qualitative content analysis by categorizing morphemes into free and bound types and interpreting their grammatical and semantic functions. The findings reveal that free morphemes, especially lexical items such as nouns, verbs, and adjectives, serve as primary carriers of semantic content and imagery, while bound morphemes—particularly inflectional suffixes such as -s, -ed, -ing, and -est—refine meaning by encoding tense, aspect, number, and degree. These morphological choices contribute significantly to thematic cohesion and emotional continuity within the song. Overall, the study demonstrates that morphology functions not only as a grammatical system but also as a vital expressive resource that enhances artistic creativity and emotional resonance in song lyrics.